Speaking Skills In Students; Comparative Study Of Regular And Upper Classes In Mts.N 1 Gorontalo Regency - Novianti, Lisa; Damhuri, Damhuri; Abdullah, Abdullah (Yayasan Daarul Qimmah Gorontalo, 2022)
This study is entitled Comparison of Speaking Skills between Superior Class Students and Regular Class Students at MTS Negeri 1 Gorontalo Regency. The purpose of this study was to see the extent of the comparison of speaking skills between featured graders and regular graders. The research method used in this study was a descriptive quantitative research method, in which the researcher used a sample of 20 superior class students and 20 students from regular classes. The method of sampling is to use a random sample system with class restrictions, namely grade 8 students. The data collection techniques in this study are interviews, oral test questions, and documentation. The results of this study are as follows: Comparison of speaking skills between superior class students and regular class students, after homogeneity test, produces data on superior classes and regular classes that have significance values above 0.05, so it can be concluded that speaking proficiency between superior class students and regular class students does not have significant differences